Role of Alcohol Advertising on Drinking Behaviors Among College Students - Steinmetz, Lora K.; Karst, Catherine A. (My University, 2011)
The purpose of this study is to further investigate the impact of alcohol advertising on college-aged students' expectancies about alcohol use, intentions to drink, and actual alcohol consumption. This research will also explore the differences in these variables between diverse ethnicities.
Color poster with text, graphs, and images.
Keywords: Posters; Advertising--Alcoholic beverages; Consumer behavior--Cross cultural studies; College students as consumers; College students--Alcohol use--Research